Transcription factor STOX1 regulates proliferation of inner ear epithelial cells via the AKT pathway - Nie, Xiaowei (Cell Prolif, 2015)
OBJECTIVES: Storkhead box 1 (STOX1) belongs to the forkhead family of transcription factors, and is reported to be involved in apoptosis of Caenorhabditis elegans. However, up to now the precise role of STOX1 in mammalian epithelial development has not been established. Here, we report that it plays an important role in regulation of proliferation of inner ear epithelial cells. MATERIALS AND METHODS: Immunohistochemistry and reverse transcription‐PCR assays were used to determine expression pattern of STOX1 in the mouse inner ear. Furthermore, its overexpression and knockdown effects on mouse inner ear epithelial cells were studied using RT‐PCR, immunofluorescence, MTT assay, BrdU labelling and western blotting. RESULTS: Storkhead box 1 was selectively expressed in epithelial cells, but not in stromal cells of the inner ear. Its over‐expression enhanced cell proliferation and sphere formation, however, STOX1 knockdown inhibited cell proliferation and sphere formation in purified utricular epithelial cells in culture. Consistently, several cell cycle regulatory genes such as for PCNA, cyclin A and cyclin E, were up‐regulated by STOX1 over‐expression. Furthermore, biochemical analyses indicated that proliferation‐promoting effects induced by STOX1 were mediated via phosphorylation of AKT in these cells. CONCLUSIONS: Taken together, we demonstrate that STOX1 is a novel stimulatory factor for inner ear epithelial cell proliferation and might be an important target to be considered in regeneration or repair of inner ear epithelium.